Exploring Resilience through Tri Hita Karana among Divorced Balinese Hindu Women - Rahmasari, Diana; Fitriana, Qurrota A’yuni; Dewi, Anak Agung Ayu Bintang Kesuma; Anggraini, Erlina; Oktaviana, Mimbar; Putri, Ellyana Ilsan Eka (Faculty of Psychology, UIN Sunan Gunung Djati, Bandung Indonesia, 2026)
Denpasar has emerged as a major locus of divorce in Bali, posing significant psychological, social, and spiritual challenges for women. This qualitative case study examined how Tri Hita Karana supports resilience among divorced Balinese Hindu women. Using purposive sampling, nine participants were recruited: three divorced Balinese Hindu women with children and employment, and six significant others (one child and one close friend for each woman). Data were collected through semi-structured, in-depth interviews and analyzed using reflexive thematic analysis. The findings show that Tri Hita Karana strengthens resilience through harmony with God (Parahyangan), fellow humans (Pawongan), and nature (Palemahan) by fostering self-acceptance, supportive relationships, autonomy, and a renewed sense of purpose. These values were reflected in gratitude, emotional recovery, and personal growth following divorce. The study underscores the cultural relevance of Tri Hita Karana as a local framework for women’s psychosocial adaptation after marital dissolution.